Surveillance to infant growth: knowledge and practice of nurses' primary health care - Altamira Pereira da Silva Reichert; Alane Barreto de Almeida; Liliana Cruz de Souza; Maria Elizabete de Amorim Silva; Neusa Collet (Universidade Federal do Ceará, 2012)
This study aimed to verify the knowledge and practice of nurses of the Family Health Strategy on the supervision of infants' growth during routine visits and maternal information on such practices. A cross-sectional quantitative study was accomplished between May and June 2009 through a questionnaire with nurses and interviews with mothers in João Pessoa, Paraíba, Brazil. For analysis, we used the EPI INFO software and the SPSS program. Nurses carried out the appointment directed to child growth and development. Nevertheless, only 37,8% of them had general knowledge on child growth; 64,4% missed the question related to the growth curve in the Child's Notebook. It was also possible to observe a contradiction between information provided by mothers and nurses on the orientation to child development. Thus, nurses need to update themselves on the contents related to children health in order to supervise child growth in a holistic way, as identified in this study.